Chemoprophylaxis and the epidemiological characteristics of re-emergent P. vivax malaria in the Republic of Korea - Changsoo Kim; Dong Chun Shin; Tai Soon Yong; Dae Kyu Oh; Rock Kwon Kim; Keeho Park; Il Suh (The World Health Organization, 2006)
OBJECTIVE: In the Republic of Korea (ROK), soldiers stationed where there is a risk of contracting malaria have received antimalarial chemoprophylaxis since 1997. However, chemoprophylaxis may facilitate the development of drug resistance, and late primary attacks in individuals who have received chemoprophylaxis are becoming more frequent. We investigated the association between chemoprophylaxis and the epidemiological characteristics and effectiveness of treatment for re-emergent Plasmodium vivax malaria, using a nationwide malaria database. METHODS: Among soldiers at risk of malaria between 1999 and 2001, we reviewed all P. vivax malaria cases (1158) that occurred before 31 December 2003. Early and late primary attacks were defined as cases occurring < 2 or > 2 months after the last day of exposure to risk of malaria, respectively. FINDINGS: Of these cases, 634 (72.0%) had received chemoprophylaxis, and 324 (28.0%) had not. Cases occurred mostly in summer, with a peak in July-August. Stratification by chemoprophylaxis history revealed different times to onset. Early primary attacks were more prevalent in the group not receiving chemoprophylaxis, while in the group receiving chemoprophylaxis most cases were late primary attacks. Of the latter, 312 out of 461 (67.7%) did not take primaquine regularly. After treatment of the first attack, 14 (1.2%) of 1158 were re-treated; all re-treated cases were cured using the same doses and regimen used for the first treatment. CONCLUSION: In ROK, the increase in late primary episodes of re-emergent P. vivax malaria is associated with the use of antimalarial chemoprophylaxis.